Antimicrobial susceptibility and multilocus sequence typing of Clostridium perfringens isolated from yaks in Qinghai-Tibet plateau, China - Wu, Dan; Luo, Runbo; Gong, Ga; Zhang, Lihong; Huang, Jiaqi; Cai, Chongzhen; Li, Yupeng; Irshad, Irfan; Song, Rende; Suolang, Sizhu (Frontiers in Veterinary Science, 2022)
Clostridium perfringens (C. perfringens) is an opportunistic pathogen that cause necrotic enteritis, food poisoning and even death in animals. In this study, we explored the prevalence, antibiotic resistance and genetic diversity of Clostridium perfringens isolated from yak in the Qinghai-Tibet plateau, China. A total of 744 yak fecal samples were collected and then the strains were assessed for toxin genes, antimicrobial susceptibility and multilocus sequence typing (MLST). Results indicated that 144 out of 744 (19.35%) yak fecal samples were tested to be positive for C. perfringens, and 75% (n=108, 108/144) were identified as C. perfringens type A, 17.36% (n=25, 25/144) were C. perfringens type C, 2.78% (n=4, 4/144) were C. perfringens type D, and 4.86% (n=7, 7/144) were C. perfringens type F. In addition, 2.78% (n=4, 4/144) of the isolates were positive for cpb2 toxin gene. Antimicrobial susceptibility testing revealed that 98.61% (142/144) of the isolates showed multiple-antibiotic resistance. According to MLST and phylogenetic tree, 144 yak-derived C. perfringens isolates had an average of 12.95 alleles and can be divided into 89 sequence types (STs) and clustered in 11 clonal complexes (CCs). Although, the most of isolates belong to type A with a considerable genetic diversity, having Simpson index up to 0.9754. MLST and phylogenetic analysis showed that the isolates under the same clade came from multiple regions. Cross-transmission among isolates and interconnectedness were observed in the genetic evolution. According to the study, the most of the isolates exhibited broad-spectrum antibacterial resistance, diverse alleles, and multiple lethal toxin genes of C. perfringens.